Evaluation of the Economic Effects of Special Economic Zones, Free Trade Zones and Port Quality - Carlucci, Fabio; Pizzutilo, Fabio; Trincone, Barbara; Venezia, Elisabetta (International Journal of Economics and Financial Issues, 2025)
This paper highlights the territorial importance of the presence of SEZs (Special Economic Zones) and FTZs (Free Trade Zones), the effects generated in macroeconomic terms, and the relevance of some contextual variables. Some research questions were asked regarding how relevant the presence or absence of SEZs/FTZs is for the purposes of attracting Foreign Direct Investments, the consequent income generated by them, the impact on foreign trade, and on the "quality of exports". These elements are investigated to detect the magnitude of the importance of the presence of SEZs/FTZs, along with a positive and welcoming context represented by variables like GDP (Gross Domestic Product), population, taxation burden, and port endowment, which are sometimes taken for granted and not quantified jointly econometrically.